Improving Students’ Vocabulary Mastery Through Media Application Online Hello English at The Seventh Grade of UPTD SMP Negeri 1 Gunungsitoli In 2022/2023 - Linda Purnama Sari Zega; Trisman Harefa; Okniel Zebua; Elwin Piarawan Zebua (Journal on Education, 2023)
This study aims to determine the use of Hello English application to Improve Students’ Vocabulary Mastery at the seventh grade of UPTD SMP Negeri 1 Gunungsitoli in 2022/2023. The researcher conducted by using Classroom Action Research. The population of the research was seventh grade of UPTD SMP Negeri 1 Gunungsitoli that considered 288 students. The research took sample which consist of 32 students in class VII-B which was chosen and suggested by English teacher. The instrument of my research is observation, field notes, test, documentation. The research conducted in two cycles that consist of two meeting of each cycle. The result of the research in cycle I showed there were 15 students did not pass the MCC of 32 students and the average of students’ mark was 65,7. In the cycle II all the students passed the MCC with the average of students’ mark was 78,2. Based on the result of the research, the researcher concluded that the used of Hello English application improved students’ vocabulary and overcome the students’ problem in this research.